Religion, spirituality and social work: an international perspective - Beth Crisp (2018)
Purpose: While there has been the emergence of a substantial body of scholarship on the place of religion and spirituality in social work, the predominant voices in this discourse have primarily been authors from the English-speaking North Atlantic countries. The purpose of this paper is to redress this issue by exploring the impact of other national perspectives. Design/methodology/approach: Using a post-colonial perspective, the author reflects on the issues which emerged in seeking to develop a truly international perspective on religion and spirituality in social work. Findings: There are important historical and contextual differences between countries which influence how social work is practiced, as well as different understandings as to what social work is. These differences are reflected in social workers’ understandings as to how religion and spirituality can be utilised in social work practice. It is also noted that the growing enthusiasm of social workers to embrace religion and spirituality in their practice needs to be tempered by the realisation that religion and spirituality can be harmful in some circumstances. Originality/value: This paper demonstrates how drawing on a wider range of international perspectives has the potential to enrich social work scholarship and practice.